Clinical outcomes of splenectomy in children: Report of the splenectomy in congenital hemolytic anemia registry. Issue 3 (24th November 2014) - Rice, Henry E.; Englum, Brian R.; Rothman, Jennifer; Leonard, Sarah; Reiter, Audra; Thornburg, Courtney; Brindle, Mary; Wright, Nicola; Heeney, Matthew M.; Smithers, Charles; Brown, Rebeccah L.; Kalfa, Theodosia; et al.
<x xml:space="preserve">Abstract</x> The outcomes of children with congenital hemolytic anemia (CHA) undergoing total splenectomy (TS) or partial splenectomy (PS) remain unclear. In this study, we collected data from 100 children with CHA who underwent TS or PS from 2005 to 2013 at 16 sites in the Splenectomy in Congenital Hemolytic Anemia (SICHA) consortium using a patient registry. We analyzed demographics and baseline clinical status, operative details, and outcomes at 4, 24, and 52 weeks after surgery. Results were summarized as hematologic outcomes, short‐term adverse events (AEs) (≤30 days after surgery), and long‐term AEs (31–365 days after surgery). For children with hereditary spherocytosis, after surgery there was an increase in hemoglobin (baseline 10.1 ± 1.8 g/dl, 52 week 12.8 ± 1.6 g/dl; mean ± SD), decrease in reticulocyte and bilirubin as well as control of symptoms. Children with sickle cell disease had control of clinical symptoms after surgery, but had no change in hematologic parameters. There was an 11% rate of short‐term AEs and 11% rate of long‐term AEs. As we accumulate more subjects and longer follow‐up, use of a patient registry should enhance our capacity for clinical trials and engage all stakeholders in the decision‐making process. Am. J. Hematol. 90:187–192, 2015. © 2014 Wiley Periodicals, Inc.